Progress in the Puzzle Resolution: The Molecular Genetics Underpinning Autism Spectrum Disorders - Alessandra Mezzelani; Francesca Anna Cupaioli (Brain Sciences, 2023)
Autism spectrum disorders (ASDs) are neurodevelopmental conditions characterized by impairments in social interaction, communication, and the presence of restricted, repetitive behaviors [...]